STUDY THE EFFECT OF BLOOD PRESSURE ON THE LEVEL OF HOMOCYSTEINE IN PATIENTS ADMITTED TO THE TIKRIT TEACHING HOSPITAL - Hussam Dawood Abdullah (Tikrit Journal of Pure Science)
This study sought to the statement of the relationship between blood pressure  and ,its impact on the level of homocysteine in the patient's blood plasma, which is a sulfur amino acid is non-essential produced compound medial during the normal process of metabolism amino acid methionine . It took patients samples of blood pressure of patients admitted in the Tikrit Teaching Hospital of (20) satisfactory sample and (10) a sample control and measured its level of homocysteine in the blood plasma, where he showed statistical analysis of the samples by comparing the samples sick with control samples very high rise significantly (P<0.001) the level of homocysteine in patients compared with healthy